Endurance athletes and skin aging: mechanisms, risks, and protective strategies - Guang, O.; Hash, M. G.; Trias, T.; Hussaini, A.; Sataray-Rodriguez, A.; Acosta, S.; Frasier, K. (Dermis, 2025)
With the growing popularity of endurance sports in recent years, endurance athletes are uniquely vulnerable to premature skin aging due to prolonged environmental exposures, high physical exertion, and training demands. This review explores factors contributing to skin aging in endurance athletes, including ultraviolet radiation, oxidative stress, chronic dehydration, and nutritional deficits. Key mechanisms such as photoaging and reactive oxygen species production are examined alongside the impacts of training intensity and insufficient recovery on skin health and aging. Strategies to mitigate these effects, including photoprotection, antioxidant supplementation, and hydration optimization, are highlighted, emphasizing their relevance to athlete-specific skincare practices. By addressing the gaps in current research and prevention, this review underscores the importance of integrating dermatologic care into endurance training to enhance both skin health and athletic longevity.